A Giant Auricular Soft Tissue Tumor Mimicking Keloid Treated with Surgical Excision and Local Advancement Flap: A Case Report: Laporan Kasus: Operasi Pengangkatan Tumor Jaringan Lunak Raksasa di Telinga yang Mirip Keloid, Diikuti dengan Teknik Tutup Kulit (Flap) Lokal - Kadek Dwi Stiti Dharma; Nyoman Siska Ananda (Universitas Pendidikan Ganesha, 2026)
Soft Tissue Tumor (STT) is a heterogeneous group of benign and malignant lesions originating from non-epithelial tissues and extraskeletal elements. These lesions may cause functional and aesthetic problems, especially when located in the head and neck area. The main treatment is surgical excision with adequate margins, followed by reconstruction if there is a large defect. Local flap is one reconstruction technique with advantages in color and texture match, while maintaining blood supply. This case report presents a 31-year-old male with a mass on the left auricle that had enlarged over two years after ear piercing. Clinical and supporting examinations, histopathological diagnosis, and tumor excision with local advancement flap were performed. A total excision of a 15 × 7 cm tumor down to the cartilage base was carried out, followed by defect reconstruction with a local advancement flap. Histopathology showed “Hyalinized Fibroma,” a benign fibrous tissue tumor with hyalinization. Postoperatively, the wound healed well without complications. Auricular soft tissue tumor excision with local flap reconstruction provided satisfactory functional and aesthetic results in cases with good local blood supply. This approach is effective in preserving auricular shape and function while minimizing postoperative complications.